Contribution of Islamic economy in achieving Sustainable Development Goals (SDGs) - Rohim, Ade Nur; Yetty, Fitri (Review of Islamic Social Finance and Entrepreneurship, 2025)
Purpose – This study aims to analyze the contribution of Islamic economics using various instruments to the achievement of Sustainable Development Goals (SDGs).Methodology – This study uses a qualitative approach with a literature study approach, with reference to various studies.Findings – This study found a close correlation and relevance between maqashid sharia as a goal of Islamic economics and the goals stated in the SDGs. In addition, it is concluded that the balance between commercial and social aspects in the Islamic economy is significant in sustainable development, which is manifested as a real contribution to the realization of the SDGs through the Islamic finance and banking sectors, as well as the Islamic social finance sector.Implications – It is recommended that the government optimize the management of various Sharia economic instruments to accelerate the achievement of the SDGs. Originality – This study emphasizes the suitability of the aim of the Islamic economic system to realize the achievement of the main maqashid sharia, namely maslahat, with the goals stated in the SDGs. It explores the contribution of the Islamic economic system in realizing sustainable development.